How do electromechanical properties of dielectric elastomer composites influence their energy harvesting performances?. (29th September 2022) - Wu, Wenju; Jiang, Yingjie; Zhong, Meilin; Liu, Suting; Yu, Bing; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract: Dielectric elastomer generators (DEGs) can harvest energy by converting mechanical energy from natural movement into electrical energy. Despite of many studies on improving the energy harvesting performances of DEG by the design of dielectric elastomer (DE) materials, how do the electromechanical properties such as dielectric constant ( ε ) and elastic modulus ( Y ) of DE materials affect their energy harvesting performances is still unclear. In this study, we purposefully designed and prepared two sets of brominated isobutylene isoprene rubber (BIIR) based DE materials, one set with almost the same ε but different Y and the other set with almost the same Y but different ε . And the effect of the single electromechanical property ( ε or Y ) on the energy harvesting performances of DEG under the cone stretching mode was revealed for the first time. In a single energy generating cycle, the generated energy and energy density are basically independent of Y, but interestingly, they sharply increase as the ε increases. Under the premise of high cone stretch displacement, DE with higher ε and lower Y has a higher electromechanical conversion efficiency. The "amplification effect" of actual generated energy with the increase in ε is quantitatively analyzed by considering the existence of charge leakage, the introduction of transfer capacitor, and the non-uniform stretching of DE film. This study provides a guidance for designing and optimizing DE materials with high energy harvesting performances. Graphical abstract: The electromechanical properties of DE materials (dielectric constant and elastic modulus) on energy harvesting performance and the tremendous "amplification effect" of actual generated energy were studied, which provide guidance for DEG with high harvesting performance. Image 1 Highlights: Two sets of samples with ε and Y as variables have been designed and prepared. The effect of ε or Y of DE on the energy harvesting performance were revealed. The energy density is independent of Y but sharply increase with increasing ε. DE with higher ε and lower Y has a higher electromechanical conversion efficiency. The amplification effect of actual generated energy with increasing ε is analyzed.